Diagnostic of Plasma Spectral and Development Ti6Al4V Alloy with Deposition Titanium Layer by R-F Sputtering - Mustafa Abdulkareem (Journal of Global Pharma Technology, 2019)
Ti6Al4V became the most favourable Titanium alloy due to its attractive mechanical and physicochemical properties and is currently extensively used e.g. in biomedical industry this work studies surface modification of Ti6Al4V to use in the implant bone. RF- sputtering is used for coating Titanium on the material Ti6Al4V alloy. The aim of this work is the power parameter (different power), used the ration power (50 watt, 100 watt, 150 watt and 200watt) the experimental Diagnostic of the coated layers by spectroscopy, FESEM and the average particle size (8.3-13.11) .The result show different colour layers, the TiN layer was shown the relationship between the electron temperature with the different power and electron density of TiN layer on Ti6 Al4V alloy with the different power (50,100,150and 200) Watt And during see the same figure the average particle size is equal for all picture between (8.3- 13.11) in the range of 100nm. The cumulative mass loss of the deposited coating specimen was about 3.71649mg for optimization samples TiN layer. The average hardness of the coating is about (264 to 331), which is higher than that of the substrate. The increases of average hardness depend on the different power.Keywords: Sputtering, Titanium, Homogenies, Implant, FESEM, Distribution, Surface modification and power.